I'm not fat, just too short for my weight: Family child care and obesity in Germany - Philippe Mahler (University of Zurich, Socioeconomic Institute, 2007)
Obesity is increasing worldwide for both adults and children. Genetic disposition is responsible for some variation in body weight but cannot explain the dramatic increase in the last two decades. The increase must be due to structural and behavioral changes. One such behavioral change is the increase in working females in the last decades. The absence from the mother reduces potential child care time in the family. Reduced child care time may have adverse effects on the prevalence of obesity in children and adults. This paper analyzes the effect of mother's labor supply in childhood on young adults probability of being obese in Germany. Using a sample drawn from the German Socio-Economic Panel the results show that a higher labor supply of the mother increases the probability for her child to be obese as young adult. This result underlines the importance of childhood environment on children's later life outcome and the importance of behavioral changes in explaining the increase in obesity.
Keywords: I12; J22; D10; 330; GSOEP; obesity; female labor supply; child care; sibling estimation; Weibliche Arbeitskräfte; Kinderbetreuung; Privater Haushalt; Gesundheitsrisiko; Kinder; Deutschland